AGECARE, MELALUI PEMBERDAYAAN PERAN KELUARGA DAN KADER PENDAMPING KELUARGA LANSIA” DI DESA LEMPER ,PAMEKASAN,MADURA - Nindawi, Nindawi; Rahman, Taufiqur; FS, Endang; Iszakiyah, Nur (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
During the Covid-19 pandemic, the elderly are a vulnerable group. The findings show that COVID-19 positive patients are dominated by the elderly, so effective efforts to protect the elderly must be implemented immediately. The vulnerability of the elderly and the efforts that can be made to deal with it. The agecare program, assisting health and family cadres in the elderly and encouraging community participation in protecting the elderly in their environment, to prepare for old age better, so that they become more Healthy, Independent, Active, Fit And Productive Elderly (HIAFP)/(SMART). Community service carried out in Lemper Pademau Pamekasan Village with a target of 15 elderly people, namely 6 men and 9 women, 15 elderly accompanying families and 5 health cadres and 1 Polindes midwife, so that there is a synchronization of cooperation and participation. Methods of implementing health education/instruction, demonstration of gymnastics and physical exercise, as well as physical and laboratory examinations. HE, Gymnastics and physical exercise followed the target (100%) and the absorption rate of theory was good-fair on average 80%. The results of the first stage of examination; Normal BMI (80%), normal blood pressure 93%, SO2 normal (93%), tachycardia (40%), and normal temperature (100%). Normal cholesterol (93%), normal uric acid (93%), normal GDA. Stage II hypertension grade 2 (33%), normal temperature (87%). SO2 is normal (93%). joint pain (40%), laboratory check normal uric acid (100%), hypercholesterolemia (80%). The role of cadres is very important to always monitor the condition of the elderly. Cadres have a role in providing information to the elderly about healthy living behavior and maintaining health during the pandemic. Another important role is cooperation with his family. Of course this should be considered so that the welfare of the elderly is also maintained, for example by providing counseling or education about the problems of physical changes experienced by the elderly. In pandemic conditions like this, the elderly need protection, and access to nutritious food, the availability of basic needs, money, medicines to support their physical health, and social care